The Inclusion of Disaster Risk Reducation in Classroom and Extra-Curricular Activities: A Case of Rural Balochistan, Pakistan - Jaffar, Khadija; Reba, Amjad; Jamil, Hazri; Azeem, Seema; Khan, Muhammad Iqbal (Universiti Utara Malaysia Press, 2024)
Abstract Purpose – Balochistan, which makes up roughly 44 percent of Pakistan’s total land area, is home to 6 percent of the nation’s inhabitants. Due to long distances and low population density, service delivery is particularly challenging. The province’s educational services are impacted by natural disasters like earthquakes, floods, droughts, and migration. Disaster risk reduction is a widely recognized concept that emphasizes appropriate education to lower an individual’s personal, familial, and communal vulnerability. The role of the school is crucial in Disaster Risk Reducation (DRR) education. As a result, the study’s goal was to explore the approaches adopted for the inclusion of DDR through teaching in classroom and school activities.